Hemangioma and its Management - Sobhan Mishra1 , Subrat Padhiary2 , Bijayalaxmi Panigrahi3 , Shibasis Biswas3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
he highest frequent benign vascular neoplasms that occur quite often in neonates & infants arehaemangiomas. Haemangiomas usually occur on the surfaces of the head and neck regions. Management ofhaemangiomasincludes wait and watch, drug therapy, sclerotherapy, cryotherapy, radiotherapy, laser therapyand surgical excision.Size, location, hemodynamic of the lesion and age of the patient are the importantconditionsthat need to consider while planning for treatment of haemangiomas.